Pelatihan Pembuatan Media Pembelajaran Berbasis Game Edukasi - Napsawati Napsawati; Agussalim Agussalim; Yusdarina Yusdarina; St. Mutia Alfiyanti Muhiddin; Muh. Tawil (JKM: Jurnal Kemitraan Masyarakat, 2023)
The development of increasingly advanced technology is a challenge for teachers, where the emergence of students' interest in games is very high so that it is not uncommon to find students prefer playing games compared to studying. So the purpose of this service is to provide training to teachers so they are able to design educational game-based learning media so that students can switch to the game. As for the method of implementing the activity, namely determining the topic or learning material to be used through tours provided by the teacher, providing the form or type of game to be made, making material cards and/or questions that support the application of the game media and the final stage is evaluating the extent to which trainees can design games. The community service activities that have been carried out are well received by the teachers and the teachers have been ableto design games according to their needs. Through this educational game application, teachers can utilize various creative elements such as pictures, videos, animations, and sounds. Teachers can use these elements to present learning material in a more interesting and fun way. This can help motivate students and make them more engaged in learning.